A comparative analysis of the location behaviour of the US and European semiconductor manufacturers - Tomokazu Arita; Philip McCann (European Regional Science Association (ERSA), 2003)
Our paper analyses micro-level data from the US and European semiconductor manufacturers. In particular, we will focus on the plants undertaking the wafer manufacturing processes. We integrate a range of production technological indices with spatial data and regional economic variables in order to understand the issues determining the location behavior of the industry. Our results indicate that the locational behaviors of the US and European wafer plants do not correspond to an orthodox product-life-cycle model.
Keywords: 330